2016
DOI: 10.4238/gmr.15017074
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin 17A gene polymorphisms and risk of coronary artery disease

Abstract: ABSTRACT. Coronary artery disease (CAD) represents a leading cause of morbidity and mortality worldwide, and genetic factors contribute to the development of this disease. We conducted a case-control study to assess the association between interleukin 17A (IL17A) rs2275913 and rs3748067 polymorphisms and development of CAD. A total of 372 CAD patients and 372 healthy controls were recruited in our investigation between January 2013 and December 2014. Genotyping of IL17A rs2275913 and rs3748067 was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Among them, 57 studies were excluded for irrelevance, three were master’s degree theses, two for predicting IL-17A polymorphisms and ischemic stroke. Finally, six studies met the criteria, including 3542 cases and 3212 controls [ 7 , 8 , 9 , 10 , 11 , 17 ]. Among them, five studies described the associations between IL-17A rs2275913 and CAD, and three studies described the associations between IL-17A rs8193037 and CAD, two studies for each described association between rs3819025, rs3748067, rs3819024 and CAD, and one study for each described association between IL-17A rs4711998, rs8193036, and CAD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, 57 studies were excluded for irrelevance, three were master’s degree theses, two for predicting IL-17A polymorphisms and ischemic stroke. Finally, six studies met the criteria, including 3542 cases and 3212 controls [ 7 , 8 , 9 , 10 , 11 , 17 ]. Among them, five studies described the associations between IL-17A rs2275913 and CAD, and three studies described the associations between IL-17A rs8193037 and CAD, two studies for each described association between rs3819025, rs3748067, rs3819024 and CAD, and one study for each described association between IL-17A rs4711998, rs8193036, and CAD.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several SNPs in IL-17A have been studied to investigate their relations with CAD risk. rs2275913 has gained the greatest attention in these involved studies, some of which found a significant association between rs2275913 and CAD [ 7 , 8 ], while others denied it [ 9 , 10 , 11 ]. Our meta-analysis did not find any relations between rs2275913 and CAD in overall analysis, but lower risk of CAD was found in GG genotype in small sample size groups when subgroup analysis was conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17A gene, which is located on chromosome 6p12.23 in human genome, encodes the IL-17A cytokine. Recently, several polymorphisms in the IL-17A gene were identified, among them, rs1974226 and rs3748067 polymorphisms in the 3’ untranslated region (3’ UTR) of the IL-17A gene, and rs2275913 polymorphism in the promoter of the IL-17A gene, which were reported to be functional in influencing individual’s susceptibility to a huge numbers of human diseases, such as gastric cancer [ 32 35 ], pulmonary tuberculosis [ 36 ], asthma [ 37 39 ], osteoarthritis [ 40 ], rheumatoid arthritis [ 41 ], and CAD [ 42 44 ]. However, to date, no study has been reported on the association between polymorphisms in the IL-17A gene and IS risk.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that several inflammatory factors contribute to the development of CAD, such as C-reactive protein, tumor necrosis factor, interleukin-6 (IL-6), IL-17A, and transforming growth factor (Zernecke et al, 2008;Yang et al, 2015;Zheng et al, 2016). An association has also been reported between IL-18 and atherosclerotic plaque rupture (de Nooijer et al, 2004), which, in turn, is believed to influence the occurrence of CAD (Opstad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%